Digital Pedagogical Approaches for Preparing South African Matric Teachers for Higher Education - Wanjiru Gachie (Noyam Journals, 2024)
South African Higher Education Institutions (HEIs) are undergoing a digital revolution, facing challenges from social, historical, and cultural diversity and low schooling backgrounds. Incorporating digital technology into teaching and learning has become essential, yet a notable digital divide persists. Students with Information Communication Technology (ICT) skills perform better in higher education compared to those from resource-restrained or marginalized communities, such as Pinetown, Durban, South Africa. This research aims to equip learners and teachers in South Africa to adapt to the rapid pace of technological change while examining the pedagogical approaches of matric teachers in digitally preparing matric learners for HEIs. A quantitative research approach was utilized to collect primary data from a sample of 363 teachers across 25 high schools in Pinetown, selected based on Krejcie and Morgan's (1970) methodology, ensuring an appropriate representation for the population of 1,300. A high response rate was achieved, facilitated by a pilot phase that clarified the research subject for participants. In addition to primary data, relevant secondary literature was also utilized. The findings revealed that a majority of teachers prefer problem-based and project-based pedagogical approaches and acknowledge the benefits of an online learning environment. These results indicate that most teachers are capable of digitally preparing matric students for higher education. Therefore, problem-based and project-based teaching and learning approaches should be emphasized in the field of digital technology. It is also recommended that teachers and lecturers in HEIs utilize online platforms to enhance the curriculum.